2001
DOI: 10.1104/pp.010244
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PSAG12-IPT Gene Expression on Development and Senescence in Transgenic Lettuce

Abstract: An ipt gene under control of the senescence-specific SAG12 promoter from Arabidopsis (P SAG12-IPT) significantly delayed developmental and postharvest leaf senescence in mature heads of transgenic lettuce (Lactuca sativa L. cv Evola) homozygous for the transgene. Apart from retardation of leaf senescence, mature, 60-d-old plants exhibited normal morphology with no significant differences in head diameter or fresh weight of leaves and roots. Induction of senescence by nitrogen starvation rapidly reduced total n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(64 citation statements)
references
References 46 publications
3
61
0
Order By: Relevance
“…Transgenic plants that express IPT genes under the control of senescence-inducible promoters show delayed chlorophyll degradation and increased productivity (Gan and Amasino 1995;McCabe et al 2001). The fact that induction of expression of GDH3 was dependent on cytokinins suggested that the cytokinin signal functions as a regulator of leaf nitrogen metabolism and productivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic plants that express IPT genes under the control of senescence-inducible promoters show delayed chlorophyll degradation and increased productivity (Gan and Amasino 1995;McCabe et al 2001). The fact that induction of expression of GDH3 was dependent on cytokinins suggested that the cytokinin signal functions as a regulator of leaf nitrogen metabolism and productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been carried out to define the mechanisms of regulation of leaf senescence, and it is suggested that some hormone signals, such as cytokinin, ethylene, salicylic acid, and jasmonate, and various environmental signals are involved in senescence (BuchananWollaston et al 2003). Cytokinins have a particular profound effect on the longevity of plant organs (Gan and Amasino 1995;McCabe et al 2001). For example, transgenic plants with increased cytokinin biosynthesis show delayed senescence and increased productivity (Gan and Amasino 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, leaf proteomes are characterized by a high dynamic range of protein concentrations that impair the proteome coverage. For instance, it has been estimated that ribulose-bisphosphate carboxylase/oxygenase (Rubisco) accounts for 40% of the total protein content of green leaves (20). In the total leaf extract, this is reflected by the identification of the large subunit of Rubisco as the top hit of the identified plant proteins, and Rubisco is clearly visible as a prominent band of around 50 kDa.…”
Section: Proteomics Analysis Of the Obligate Pathogen B Graminis-a Smentioning
confidence: 99%
“…Cytokinins have been found to play a role in delaying leaf senescence (Gan and Amasino, 1995;McCabe et al, 2001;Kim et al, 2006), whereas ethylene, jasmonates (JAs), brassinosteroids, and salicylic acids are known to promote the process of senescence (Grbic and Bleecker, 1995;Oh et al, 1997;Morris et al, 2000;Jing et al, 2002;Yin et al, 2002). For example, JA could rapidly induce the expression of several SAGs (Park et al, 1998;Schenk et al, 2000).…”
mentioning
confidence: 99%